2013
DOI: 10.2320/matertrans.m2012341
|View full text |Cite
|
Sign up to set email alerts
|

Stress Corrosion Cracking Behavior of Zirconium in Boiling Nitric Acid Solutions at Oxide Formation Potentials

Abstract: Zirconium has been utilized in nuclear fuel reprocessing plants because of its superior corrosion resistance in nitric acid solutions. However, stress corrosion cracking (SCC) susceptibility of zirconium has been reported in boiling nitric acid solutions at the passivity breakdown potential. However, it has not been clear the SCC initiation and propagation behavior of zirconium.In this study, to clarify the SCC initiation and propagation behavior of zirconium, constant load tensile tests were carried out in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Nagano et al [21] noted that a passive oxide film in pure zirconium and its alloys ruptured because of stress in corrosive environments depending on temperature and HNO 3 concentration. Several other studies have reported on the stress-based corrosion cracking in zirconium and its alloys [22][23][24][25]. A high residual stress gradient can result in rapid delamination of welded plates within a few seconds after the collision of plates in the case of improper welding parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Nagano et al [21] noted that a passive oxide film in pure zirconium and its alloys ruptured because of stress in corrosive environments depending on temperature and HNO 3 concentration. Several other studies have reported on the stress-based corrosion cracking in zirconium and its alloys [22][23][24][25]. A high residual stress gradient can result in rapid delamination of welded plates within a few seconds after the collision of plates in the case of improper welding parameters.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 SCC has been the subject of study in recent years for different materials, because of the enormous damage it causes in structures. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] The susceptibility of DSSs to SCC has recently been studied by Laitinen and Hanninen 27 who investigated SCC susceptibility in a 50 wt-% CaCl 2 solution at 100°C for the UNS S31803 DSS. They observed that crack propagation was mainly through the austenite phase.…”
Section: Introductionmentioning
confidence: 99%
“…A nobler corrosion potential causes a breakdown in the passivated film and increases the SCC susceptibility in nitric acid solutions [7]. Recently, an investigation of the SCC of zirconium in nitric acid solutions CONTACT Chiaki Kato kato.chiaki@jaea.go.jp concluded that the tarnish rupture of a grown thick zirconium oxide film during anodic oxidization is a convincing SCC mechanism [8]. However, the relationship between the orientation of the zirconium plate and the growth properties of the zirconium oxide film related to SCC was not fully studied.…”
Section: Introductionmentioning
confidence: 99%